Accumulation of the delivered treatment dose in volumetric modulated arc therapy with breath-hold for pancreatic cancer patients based on daily cone beam computed tomography images with limited field-of-view - Ziegler, Marc; Nakamura, Mitsuhiro; Hirashima, Hideaki; Ashida, Ryo; Yoshimura, Michio; Bert, Christoph; Mizowaki, Takashi (Medical Physics, 2019)
Background and purpose: Inter-fractional changes of the daily anatomy of the patient are a source of error in radiotherapy. This effect is especially present in the abdomen, where there are daily differences in the filling of the stomach or the intestines. This study investigated the impact of inter-fractional changes of pancreatic cancer patients who underwent breath-hold volumetric modulated arc therapy on the applied dose by using deformable image registration. Material and methods: Deformable image registration was used to determine a displacement field which maps the computed tomography (CT) used for treatment planning onto daily breath-hold cone-beam CT images with limited field-of-view (FOV) which were acquired at the beginning of every treatment fraction. Different B-spline registration methods utilizing different metrics and regularizations were used and compared. The resulting deformed planning CT images were used to calculate the dose distributions on the anatomy of the day which can therefore be seen as a good estimation of the actually delivered dose during the treatment fractions. Additionally, the accumulated dose distribution was determined by accumulating all daily dose distributions using inverted deformation fields. The calculated dose distributions were then compared to the planned dose by comparison of dose volume histograms and dosimetric volumetric indices. Results: Best registration results were obtained using a gradient magnitude metric and a regularization of λ = 0.05. The accumulated dose distributions showed that the mean dose delivered to the clinical target volume was on median reduced by 0.61 Gy after 15 fractions from the planned dose. For the organs at risk, the accumulated dose distributions were still fulfilling all clinical goals for the patient cohort used in this study. It was found that rotating and shearing motions of the tumor led to a greater reduction in the mean target dose which correlated with the proximity of the target to the spine (r = 0.54, P = 0.038). Conclusion: With the proposed method, it is possible to generate a deformed planning CT image which matches the anatomy of the day based on cone beam computed tomography images with a limited FOV and calculating the dose distribution of the day. The dosimetric impact of the inter-fractional variations was small for most patients but showed larger deviations if the tumor is located in close proximity to the spine.
CRIS-Team Scopus Importer:2019-06-28
Keywords: breath-hold; deformable image registration; inter-fractional changes; pancreatic cancer

Choosing a reference phase for a dynamic tumor tracking treatment: A new degree of freedom? - Ziegler, Marc; Lettmaier, Sebastian; Fietkau, Rainer; Bert, Christoph (Medical Physics, 2019)
Purpose: With the introduction of dynamic tumor tracking in radiotherapy, it is possible to irradiate moving targets with minimal safety margins. However, most dynamic tumor tracking techniques rely on changing the beam geometry by, for example, adapting the multileaf collimator (MLC) positions or rotating the LINAC head. These changes are relative to a reference position which is determined by a specific breathing phase. Since these changes in the beam path also influence the delivered dose, choosing a different reference position based on a different breathing phase impacts the applied dose to the patient. This work investigates the influence of choosing different reference breathing phases on the dose distribution. Methods: The Vero system tracks the moving target by performing a pan and tilt rotation of the LINAC head. For 13 patients, the target position was extracted from every phase of a four-dimensional computed tomography (4DCT) and the pan and tilt values were determined with respect to three different reference phases. These reference phases were inspiration, expiration, and the midventilation. For all reference phases, a 4D dose calculation was performed on the 4DCT regarding the respective pan and tilt values. Furthermore, the applied dose to the target and surrounding organs at risk was calculated. To accumulate the dose distribution, weights from the actual patient breathing motion were determined. The weights were calculated from the breathing motions from different days to investigate the impact of daily variations in the breathing motion onto the accumulated dose distribution. All obtained values were then compared to the static treatment plan. Results: The mean and maximum doses applied to the target or surrounding organs at risk show no general behavior depending on the different reference phases. Nevertheless, for some patients, large differences (approx. 30%) in the applied dose to certain organs at risk could be observed, whereas the applied dose to the target shows no dependency on the different reference phases. However, the mean target dose is in all cases approx. 1.5% below the reference value from the static treatment plan. Conclusion: Although no general dependency of the applied dose on the selected reference phase could be found, the choice of the reference phase can have great impact on the organ at risk dose for some patients. Thus, the choice of the reference phase used for patient positioning should be considered during treatment planning since it can be seen as a new degree of freedom of a treatment based on tracking.
CRIS-Team Scopus Importer:2019-07-16
Keywords: 4D dose calculation; dynamic tumor tracking; liver cancer; lung cancer

Dose calculation and verification of the Vero gimbal tracking treatment delivery - Prasetio, Heru; Wölfelschneider, Jens; Ziegler, Marc; Serpa, M.; Witulla, Barbara; Bert, Christoph (Physics in Medicine and Biology, 2018)
The Vero linear accelerator delivers dynamic tumor tracking (DTT) treatment using a gimbal motion. However, the availability of treatment planning systems (TPS) to simulate DTT is limited. This study aims to implement and verify the gimbal tracking beam geometry in the dose calculation. Gimbal tracking was implemented by rotating the reference CT outside the TPS according to the ring, gantry, and gimbal tracking position obtained from the tracking log file. The dose was calculated using these rotated CTs. The geometric accuracy was verified by comparing calculated and measured film response using a ball bearing phantom. The dose was verified by comparing calculated 2D dose distributions and film measurements in a ball bearing and a homogeneous phantom using a gamma criterion of 2%/2 mm. The effect of implementing the gimbal tracking beam geometry in a 3D patient data dose calculation was evaluated using dose volume histograms (DVH). Geometrically, the gimbal tracking implementation accuracy was <0.94 mm. The isodose lines agreed with the film measurement. The largest dose difference of 9.4% was observed at maximum tilt positions with an isocenter and target separation of 17.51 mm. Dosimetrically, gamma passing rates were >98.4%. The introduction of the gimbal tracking beam geometry in the dose calculation shifted the DVH curves by 0.05%-1.26% for the phantom geometry and by 5.59% for the patient CT dataset. This study successfully demonstrates a method to incorporate the gimbal tracking beam geometry into dose calculations. By combining CT rotation and MU distribution according to the log file, the TPS was able to simulate the Vero tracking treatment dose delivery. The DVH analysis from the gimbal tracking dose calculation revealed changes in the dose distribution during gimbal DTT that are not visible with static dose calculations.
EVALuna2:33026

Examination of a deformable motion model for respiratory movements and 4D dose calculations using different driving surrogates - Wölfelschneider, Jens; Seregni, Matteo; Fassi, Aurora; Ziegler, Marc; Baroni, Guido; Fietkau, Rainer; Riboldi, Marco; Bert, Christoph (Medical Physics, 2017)
PURPOSE: The aim of this study was to evaluate a surrogate-driven motion model based on four-dimensional computed tomography that is able to predict CT volumes corresponding to arbitrary respiratory phases. Furthermore, the comparison of three different driving surrogates is examined and the feasibility of using the model for 4D dose re-calculation will be discussed. METHODS: The study is based on repeated 4DCTs of twenty patients treated for bronchial carcinoma and metastasis. The motion model was estimated from the planning 4DCT through deformable image registration. To predict a certain phase of a follow-up 4DCT, the model considers inter-fractional variations (baseline correction) and intra-fractional respiratory parameters (amplitude and phase) derived from surrogates. The estimated volumes resulting from the model were compared to ground-truth clinical 4DCTs using absolute HU differences in the lung region and landmarks localized using the Scale Invariant Feature Transform. Finally, the γ-index was used to evaluate the dosimetric effects of the intensity differences measured between the estimated and the ground-truth CT volumes. RESULTS: The results show absolute HU differences between estimated and ground-truth images with median value (± standard deviation) of (61.3 ± 16.7) HU. Median 3D distances, measured on about 400 matching landmarks in each volume, were (2.9 ± 3.0) mm. 3D errors up to 28.2 mm were found for CT images with artifacts or reduced quality. Pass rates for all surrogate approaches were above 98.9% with a γ-criterion of 2%/2 mm. CONCLUSION: The results depend mainly on the image quality of the initial 4DCT and the deformable image registration. All investigated surrogates can be used to estimate follow-up 4DCT phases, however, uncertainties decrease for volumetric approaches. Application of the model for 4D dose calculations is feasible.
EVALuna2:32902

Examination of Gold Marker Detection in Tracking Treatments of Liver Cancer Patients using Vero SBRT System - Ziegler, Marc; Brandt, Tobias; Lettmaier, S.; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (2018)
EVALuna2:36476

Examination of the automatic fiducial marker detection on the Vero system - Ziegler, Marc; Brandt, Tobias; Lettmaier, S.; Fietkau, Rainer; Bert, Christoph (2018)
EVALuna2:36478

Is adaptive treatment planning in multi-catheter interstitial breast brachytherapy necessary? - Kallis, Karoline; Ziegler, Marc; Lotter, Michael; Kreppner, Stephan; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Radiotherapy and Oncology, 2019)
Purpose: For 55 patients treated with interstitial multi-catheter breast brachytherapy the need for adaptive treatment planning was assessed. Methods and materials: For all patients a treatment planning computed tomography (CT) and a follow-up CT were acquired and used for the retrospective evaluation. Keeping dwell time and dwell positions constant, the treatment plan assessed directly after catheter implantation was compared to the situation 48 h after implantation. Both manual catheter reconstructions, based on the planning and follow-up CT, were rigid registered to each other and the resulting deviations analyzed, like the difference between corresponding dwell positions (ΔDP) or the discrete Fréchet distance. Further, the dosimetric changes, e.g., coverage index (ΔCI), conformal index (ΔCOIN) and dose non-uniformity ratio (ΔDNR) were considered for a deformed planning target volume (PTV) and the rigid warped PTV structure. The PTV was deformed according to the vector field estimated between the two acquired CTs. Results: Over all patients with rigid aligned CTs a mean ΔDP, ΔCI, ΔCOIN and ΔDNR were determined to 2.41 ± 1.73 mm, 3.10 ± 3.17%, 0.009 ± 0.007 and 0.036 ± 0.040, respectively. Considering the deformed PTV ΔCI was estimated to 5.05 ± 4.14 %. Conclusion: In conclusion, in 4% of the cases re-planning would have been beneficial to ensure the planned dose delivery. Large PTV changes or large DP deviations were found to be the main reasons for dosimetric variations.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Adaptive treatment planning; Breast cancer; Deformable image registration; Interstitial brachytherapy

Method for a motion model based automated 4D dose calculation - Ziegler, Marc; Brandt, Tobias; Lettmaier, Sebastian; Fietkau, Rainer; Bert, Christoph (Physics in Medicine and Biology, 2019)
The Vero system can treat intra-fractionally moving tumors with gimbaled dynamic tumor tracking (DTT) by rotating the treatment beam so that it follows the motion of the tumor. However, the changes in the beam geometry and the constant breathing motion of the patient influence the dose applied to the patient. This study aims to perform a full 4D dose reconstruction for thirteen patients treated with DTT at the Vero system at the Universitätsklinikum Erlangen and investigates the temporal resolution required to perform an accurate 4D dose reconstruction. For all patients, a 4DCT was used to train a 4D motion model, which is able to calculate pseudo-CT images for arbitrary breathing phases. A new CT image was calculated for every 100 ms of treatment and a dose calculation was performed according to the current beam geometry (i.e. the rotation of the treatment beam at this moment in time) by rotating according to the momentary beam rotation, which is extracted from log-files. The resulting dose distributions were accumulated on the planning CT and characteristic parameters were extracted and compared. [Formula: see text]-evaluations of dose accumulations with different spatial-temporal resolutions were performed to determine the minimal required resolution. In total 173 700 dose calculations were performed. The accumulated 4D dose distributions show a reduced mean GTV dose of 0.77% compared to the static treatment plan. For some patients larger deviations were observed, especially in the presence of a poor 4DCT quality. The [Formula: see text]-evaluation showed that a temporal resolution of 500 ms is sufficient for an accurate dose reconstruction. If the tumor motion is regarded as well, a spatial-temporal sampling of 1400 ms and 2 mm yields accurate results, which reduces the workload by 84%.
CRIS-Team Scopus Importer:2019-11-26

Performance of gimbal-based dynamic tumor tracking for treating liver carcinoma - Ziegler, Marc; Brandt, Tobias; Lettmaier, Sebastian; Fietkau, Rainer; Bert, Christoph (Radiation Oncology, 2018)
BACKGROUND: Since the introduction of tumor tracking in radiotherapy, it is possible to ensure a precise irradiation of moving targets. To follow the tumor movement, most systems rely on the detection of implanted markers and correlation models between the internal and external patient movement. This study reports the clinical workflow and first results of the dynamic tumor tracking (DTT) performance for patients with liver carcinoma at the Vero SBRT system of the University Hospital Erlangen regarding the detection of the internal marker and the changes of the determined correlation models. METHODS: So far 13 liver patients were treated with DTT. For each patient, two fiducial markers (FM), which are monitored with X-rays during treatment, were implanted in the vicinity of the tumor. All patients received a fraction dose of 4-6 Gy with 8 to 12 fractions. Treatment and patient data is evaluated by processing the acquired log-files of the DTT treatment. Based on this, the marker detection and the changes of the correlation model between the internal and external movement is investigated. RESULTS: The median treatment time was 19:42 min. During treatment a median of 173 X-ray stereoscopic images were acquired. The marker detection was successful in 64.6% of the images. The FM detection is independent of the relative angle between the marker and the imager, but shows a dependency on the average intensity surrounding the FM position within the kV images. The number of correlation models needed during treatment increases in the presence of baseline shifts. The comparison of the correlation models shows large differences in the internal-external correlation between the different models acquired for one patient. CONCLUSION: Thirteen liver patients were treated with DTT at the Vero SBRT system and the marker detection was analyzed. Furthermore, the importance of regularly monitoring the internal target motion could be shown, since the correlation between the internal and external motion changes considerably over the course of the treatment.
EVALuna2:36448

Performance of Makerless Tracking for Gimbaled Dynamic Tumor Tracking - Ziegler, Marc; Lettmaier, Sebastian; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2019)
Background and Purpose: The purpose of this work is to report the workflow and the accuracy of the new markerless dynamic tumor tracking (MLDTT) method of the Vero 4DRT system introduced with ExacTrac 3.6.1. Material and Methods: Phantom measurements were performed to assess the accuracy of the MLDTT algorithm by using the QA-tool which is provided by the vendor. A patient breathing curve was used as the motion trajectory of the phantom and the target positions detected by the MLDTT algorithm were compared to the defined positions. Furthermore, eight patients have been treated with MLDTT between May 2018 and July 2019. A log-file analysis is used to evaluate MLDTT treatment data. Results: The accuracy of the MLDTT detection is 0.12 mm ± 0.12 mm, 0.12 mm ± 0.11 mm, 0.20 mm ± 0.21 mm for the x-, y-, z-direction, respectively. These values are comparable to the accuracy of marker based DTT at the Vero system. The median treatment time was 21 min 34 seconds and 175 kV images were acquired during treatment for monitoring the target motion. Conclusion: The accuracy of the MLDTT algorithm is comparable to the marker based approach and the accuracy reported for the XSight Lung of the CyberKnife. Eight patients were treated successfully using MLDTT and the treatment times are comparable to a standard DTT treatment.
CRIS-Team Scopus Importer:2019-12-27
Keywords: NSCLC; Real-time monitoring; Stereotactic body radiation therapy; Tumor Tracking

Performance of Marker-less Tracking for Gimbaled Dynamic Tumor Tracking - Ziegler, Marc; Lettmaier, S.; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-06-18

Quality assurance for dynamic tumor tracking - Witulla, Barbara; Ziegler, Marc; Brandt, Tobias; Prasetio, Heru; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2021)
The purpose of this work was to develop a treatment plan verification routine for a linear accelerator dedicated to SBRT treatments with gimbal based dynamic tumor tracking using three commercially available phantoms. The accelerator system has two special features: It operates with a rotation of the ring shaped gantry instead of a couch rotation and target motion can be compensated for via a gimbal system (dynamic tumor tracking, DTT). DTT plans were each measured with the three different phantoms. Afterwards the measured dose distribution was compared with the calculated dose distribution via global Gamma Index analysis (3 mm / 3%, threshold: 10%). The global gamma pass rates were on average (93.5 ± 7.2) % for ArcCHECK, (98.0 ± 2.6) % for OCTAVIUS® 4D and (98.4 ± 4.2) % for MatriXX Evolution. All three systems could be used for quality assurance with ring rotations and DTT, however, each with limitations.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Intensity modulated radiation therapy; quality assurance; Stereotactic body radiation therapy; Tumor Tracking